DETERMINATION OF SUSCEPTIBILITY OF ANOPHELES SACHAROVI COLLECTED FROM DASHT ARGEN IN FARS PROVINCE TO DDT, MALATHION FENITROTHION (DIPTERA, CULICIDAE) - S. Ghavami; H.Ladonni (Tehran University of Medical Sciences, 1999)
To determine the degree of susceptibility of An. Sacharovi to malathion 5%, fenitrothion 1% and DDT 4% extended studies were carried out on sucked blood engorged mosquitoes collected from Dasht Argen (Fars province) in 1997. Testing method was according to standard WHO method in lots of 25 adults' mosquitoes in 4 replicates. An. Sacharovi were touched by malathion 5% and DDT 4% insecticides in 15, 30 and 60 minutes exposure time. Based on the results, mortality level was found to be 53.1%, 84.3% and 100% for malathion and 48.5%, 85.4% and 100% for D.D.T. LD50 and LD90 for DDT was found to be 15.70 and 32.55 min, respectively. According to the results, An. Sacharovi was susceptible to malathion and D.D.T. However, this Anophel had strong resistance background to D.D.T. in other areas in Iran. Another insecticide tested was fenitrothion with 1% in 60, 75, 90 and 120 min exposure time mortality was 35.4%, 60.6%, 64.3% and 84.5%, with LD50 and LD90 of about 69.83 and 138.9 min, respectively. Due to absence of fenitrothion application in malaria vectors control program in southern Iran and also susceptibility to malathion, it seems that the fenitrothion dosage of 1% in 120 min time might not be effective, therefore, it is recommended to change that concentration of insecticide or the amount of exposure time.